The state of the art: object retrieval in paintings using discriminative regions - Crowley, E; Zisserman, A (British Machine Vision Association, 2014)
The objective of this work is to recognize object categories (such as animals and vehicles) in paintings, whilst learning these categories from natural images. This is a challenging problem given the substantial differences between paintings and natural images, and variations in depiction of objects in paintings. We first demonstrate that classifiers trained on natural images of an object category have some success in retrieving paintings containing that category. We then draw upon recent work in mid-level discriminative patches to develop a novel method for re-ranking paintings based on their spatial consistency with natural images of an object category. This method combines both class based and instance based retrieval in a single framework. We quantitatively evaluate the method over a number of classes from the PASCAL VOC dataset, and demonstrate significant improvements in rankings of the retrieved paintings over a variety of object categories.